«Une des figures les plus originales de Milan»: the art dealer Giuseppe Baslini (1817-1887) (ACME, 2022)
This article aims to investigate the many faces of a key figure in the European art market of the 19th century, to which studies have not yet paid due attention: the dealer Giuseppe Baslini. Recognised by his contemporaries for his exceptional talent as a connoisseur and his unscrupulous business flair, Baslini was probably the most important Milanese art dealer of the second half of the 19th century. His shop in via Montenapoleone 11 became a reference point and a place of attraction for restorers, collectors and travelling agents from all over Europe. Moreover, Baslini was a consultant and supplier to the Poldi Pezzoli and Bagatti Valsecchi collections in Milan, which took advantage of his variety of interests, but also to the National Gallery in London and the Gemäldegalerie in Berlin. His “perfidious business”, as well as his role as a mediator for galleries and private collections, are documented by the letters of Giovanni Morelli and Austen Henry Layard, by the travel notebooks of Charles Eastlake and Otto Mündler and by the autobiography of Wilhelm von Bode. The reconstruction of the antiquarian’s biographical and professional history, based on unpublished archive documents, letters, invoices and auction catalogues, has revealed an attractive and controversial personality, important medium for discovering unknown relationships and provenances.
Keywords: Milano; art dealer; art market; collecting; connoisseurship; XIX century